Determinan Pertumbuhan Ekonomi ASEAN+5: Aspek Lingkungan - Sari, Kartika; Wahyudi, Setyo Tri; Nabella, Rihana Sofie (UI Scholars Hub, 2023)
The environmental aspect is a vital issue because it is closely related to economic activities that drive the rate of economic growth. Environmental aspects in this study are environmental degradation and natural resource rent. Natural resource rent is still considered a curse or a blessing for a country. Therefore, this study aims to determine the effect of environmental aspects in terms of environmental degradation and natural resource rent. In addition, in this study, foreign direct investment and life expectancy were also selected to determine their effect on economic growth. This study took a sample of 5 countries in the ASEAN+ 5 region using panel data analysis for the period 1990 to 2018. The results obtained were environmental degradation, natural resource rents and foreign direct investment had a significant positive effect on economic growth. Life expectancy does not significantly affect economic growth.